The Japanese finance corporate finance and capital markets in changing Japan - Choi, Jongmoo Jay, 1945-; Hiraki, Takato (International finance review,, 2003)
Japan has always been an odd man out from the standpoint of Western norm or Western finance. It is a country that is as developed as any in the West. However, it is also a country that possesses the significant institutional and cultural traits that separate it from the West. An important question in finance is to what extent the basic models of finance, developed with the Western perfect market view in mind, can be applied to Japan; or conversely, what critical adjustments must be made to make models amendable to the reality of Japanese finance. This book contains 21 substantive papers that address various aspects of Japanese finance. This is an attempt to bring them together under the same cover so that the commonality and peculiarity of Japanese finance can be more easily discerned across different applications as well as compared across countries. Hence, despite apparent differences in topics, the theme is international and comparative in nature throughout.